Forward programming of hPSCs to neutrophils using chemically defined media - Hayley E. Hall; Xiaoping Bao; Cheng Dong; Xiaojun Lance Lian (Stem Cell Research & Therapy)
Abstract Polymorphonuclear neutrophils (PMNs), the most abundant leukocytes circulating in human blood, are pivotal players in the innate immune system. In recent years, PMNs have gained increasing recognition for their significant involvement in the pathogenesis of a wide array of human diseases, including sepsis, pulmonary conditions, autoimmune disorders, and various cancers. Due to their terminally differentiated state, PMNs possess a short lifespan and exhibit limited proliferative potential, which makes continuous replenishment from the bone marrow essential for maintaining immune homeostasis. This demand underscores the need for efficient, reliable, and robust methods of PMN production. In this study, we evaluated three forward programming protocols and one directed differentiation protocol aimed at generating PMNs from human pluripotent stem cells (hPSCs). We analyzed not only their differentiation efficiency but also the transcriptomic profiles and functional capabilities of the resulting PMNs. Our findings revealed that both the forward programming method and the directed differentiation approach can successfully generate functional PMNs. Furthermore, by fine-tuning the culture media at various stages during forward programming, we identified an optimal protocol that significantly enhances hematopoietic differentiation potential and promotes the functional maturity of the neutrophils.